Discrimination between pressure and fluid saturation changes from time-lapse seismic data at a CO2 storage site - Ivanova, A.; Yang, C.; Kummerow, J.; Lueth, S.; Juhlin, Christopher (Society of Petroleum Engineers, 2011)
Capture and geological storage of CO2 are an option to reduce greenhouse gas emissions. At Ketzin (Germany), the first European onshore pilot scale project was initiated in 2004. For this project, 3D time-lapse surveys are an essential tool for high resolution reservoir characterization. A baseline and a smaller repeat survey were acquired in Autumn 2005 before the injection and in Autumn 2009 after 22 kilotons of CO2 had been injected respectively. Seismic differences between the baseline and the monitor survey were previously interpreted as a fluid saturation effect only. However, for some fields undergoing injection both fluid and pressure changes have approximately the same degree of impact on seismic data. Landro (2001) described a method based on AVO analysis to discriminate the both types of changes directly from 3D time-lapse data for an oil-water contact. In this study we apply this method to a case of CO2 injection into a saline aquifer. We were able to detect the CO2 propagation in the reservoir, but currently a low signal-noise ratio prevents a clear discrimination between changes caused by fluid saturation and by pore pressure.